The impact of anger on donations to victims - Doorn, Janne van (International review of victimology, 2017)
This article investigates if and when anger appeals (communications that elicit anger in people), can be used to increase donations to charity. In an experimental study the idea was tested that anger leads to higher charitable donations, under the condition that people can restore equity with that donation (i.e., restore the harm done to the victim). Results indeed show that when one’s donation serves a specific restorative function (i.e., compensates the suffering of women so that they can start a new life) as compared to a non-restorative function (i.e., offers help in special crisis centers for women, to alleviate their suffering and not worsen their situation), angry participants donated more to charity. This difference was absent when people did not experience anger. Furthermore, angry people donated more to the restorative charity than people not experiencing this emotion. The effect of anger on charitable donations occurred independently from people’s empathic concern. These results thus suggest that anger can act as an emotional appeal in soliciting charitable donations.